Organizational characterization of craftsmanship in northern of Valle del Cauca - Betancourt Guerrero, Benjamín; Espinal Ruiz, Dario José; Scarpetta Calero, Gildardo (Cuadernos de Administración, 2020)
Young creators, designers, and master artisans are reinventing craftsmanship with their freshness and daring and turning it into a laboratory for sensory, emotional, and symbolic experiences. This paper will present artisans’ organizational status in the development of such a profession or craft in the municipalities that are part of the northern region of Valle del Cauca (Colombia). For this purpose, we resorted to documentary analysis and inquiries with stakeholders to characterize the region socially and demographically, for its geographical location, and identifying comparative and competitive advantages in the territory, according to the productive vocation of the municipalities and their relationship with crafts production. Likewise, the research analyzes artisans’ capabilities as a dynamizing sector for social, economic, and organizational processes. This study is a preliminary approach because its results are inconclusive, thus allowing other researchers to develop into the importance of the artisanal sector for the socio-economic development of the northern region of Valle del Cauca. The strategic approaches outlined in this paper are those consolidated with the stakeholders, who have enabled the craft sector’s strengthening through innovative proposals regarding the management of their workshops and business units.